Diagnostic accuracy of prenatal imaging for the diagnosis of congenital Zika syndrome: Systematic review and meta-analysis - Herrera, Tania T.; Cubilla-Batista, Idalina; Goodridge, Amador; Pereira, Tiago V. (Frontiers in Medicine, 2022)
Objective The aim of this study was to assess the accuracy of prenatal imaging for the diagnosis of congenital Zika syndrome. Data sources Medline (via Pubmed), PubMed, Scopus, Web of Science, and Google Scholar from inception to March 2022. Two researchers independently screened study titles and abstracts for eligibility. Study eligibility criteria Observational studies with Zika virus-infected pregnant women were included. The index tests included ultrasound and/or magnetic resonance imaging. The reference standard included (1) Zika infection-related perinatal death, stillbirth, and neonatal death within the first 48 h of birth, (2) neonatal intensive care unit admission, and (3) clinically defined adverse perinatal outcomes. Synthesis methods We extracted 2 × 2 contingency tables. Pooled sensitivity and specificity were estimated using the random-effects bivariate model and assessed the summary receiver operating characteristic (ROC) curve. Risk of bias was assessed using QUADAS 2 tool. The certainty of the evidence was evaluated with grading of recommendations. Results We screened 1,459 references and included 18 studies (2359 pregnant women, 347 fetuses with confirmed Zika virus infection). Twelve studies (67%) were prospective cohorts/case series, and six (37%) were retrospective cohort/case series investigations. Fourteen studies (78%) were performed in endemic regions. Ten studies (56%) used prenatal ultrasound only, six (33%) employed ultrasound and fetal MRI, and two studies (11%) used prenatal ultrasound and postnatal fetal MRI. A total of six studies (ultrasound only) encompassing 780 pregnant women (122 fetuses with confirmed Zika virus infection) reported relevant data for meta-analysis (gestation age at which ultrasound imagining was captured ranged from 16 to 34 weeks). There was large heterogeneity across studies regarding sensitivity (range: 12 to 100%) and specificity (range: 50 to 100%). Under a random-effects model, the summary sensitivity of ultrasound was 82% (95% CI, 19 to 99%), and the summary specificity was 97% (71 to 100%). The area under the ROC curve was 97% (95% CI, 72 to 100%), and the summary diagnostic odds ratio was 140 (95% CI, 3 to 7564, P < 0.001). The overall certainty of the evidence was “very low”. Conclusion Ultrasound may be useful in improving the diagnostic accuracy of Zika virus infection in pregnancy. However, the evidence is still substantially uncertain due to the methodological limitations of the available studies. Larger, properly conducted diagnostic accuracy studies of prenatal imaging for the diagnosis of congenital Zika syndrome are warranted. Systematic review registration Identifier [CRD42020162914].